Teachers’ Questions in the Classroom - Vijaysimha, Indira (Voices of Teachers and Teacher Educators, 2019)
The paper presents a case study of how a well thought out teacher develop program can contribute positively towards innovative education of tribal children. The paper draws upon classroom observation of teacher’s practices, children’s reading writing and comprehension (pre, mid and post) in project schools and control schools and qualitative data from teacher and student interviews. By enabling teachers as professionals through professional development and not just training, it was possible to create an ecosystem where all stakeholders were invested in the education process. This study indicates that the successful implementation of the new practice results in improved reading ability, visible increase in student attendance and greater student interest towards school. While indigenous peoples make up around 5% of the global population, they account for approximately 15% of the world’s extreme poor, and regularly appear at the bottom of human well-being index ratings. One of the key causes for this is the lack of quality education delivered through culturally appropriate teaching strategies. The primary focus of this paper is to explore the how a professional approach toteacher development enabled an ecosystem where children have better reading and writing ability than average. The NGO, Agragamee has developed a unique reading and writing program for children in the first three years of schooling. Children in Agragamee School achieved fluency and were easily able to cope with the standard textbooks of Odisha state by the time they entered class III. By reducing dropout rates the method had increased the chances of success of students in school while encouraging the teachers to be invested in the education process. Due to the success, Agragamee was awarded a grant to test this method in 18 government schools across three districts. Key to the implementation of this method was preparing teachers to adopt and engage with the creative language development processes. Young, fresh support teacherswere hired and to overcome the challenge of de-schooling teachers used to traditional pedagogies. A series ofteacher development workshops for the support teachers was conducted. New content and material to support the reading and writing program were developed and the teachers were familiarized with these.